Motivation and performance of students of an engineering program in the realization of industrial practices (2018)
Industrial internships become the first approach to working life for students in their last semester and the first approach to develop the skills learned during their professional training. The Industrial Engineering program of the Francisco de Paula Santander University monitors the performance of the industrial practices and the motivation reflected by the students in the company where they carry out the practices. The article shows the results in the development of industrial practices, in terms of student motivation and performance in the tasks assigned in the company, highlighting the strengthening of professional development of students of industrial engineering.